Utilização de criptomoedas como forma de pagamento pelo comércio lojista - Malaguti, Bruno (2023)
The means of payment are being updated, internet commerce is growing and competitiveness is gradually developing, making it necessary for the retailer to find ways to have a significant advantage over its competitors. The objective of this work is to present to entrepreneurs an alternative way of payment that is in growth, showing positive and negative points in relation to the current means of payment. A payment gateway tool was presented, which automatically converts to local currency, with attractive rates if the merchant chooses to do so. The methodological procedure used consists of reviews based on bibliographical research carried out from books, academic articles, and periodical websites, with the objective of presenting a theoretical basis on means of exchange and its evolutions, currencies, innovations, and technologies that preceded virtual currency. Bitcoin. It is concluded that in this perspective of constant advances, there is a need for the shopkeeper to keep up to date with regard to technology and means of payment. It is important that the merchant evaluates the positives, negatives, and challenges when adopting the payment method. Commerce does not necessarily need to adopt cryptocurrencies as a substitute for traditional currencies, but can use it as an alternative payment system.